Lipid-dependent regulation of the unfolded protein response. (April 2015) - Volmer, Romain; Ron, David
Abstract : Protein folding homeostasis in the lumen of the endoplasmic reticulum is defended by signal transduction pathways that are activated by an imbalance between unfolded proteins and chaperones (so called ER stress). Collectively referred to as the unfolded protein response (UPR) this homeostatic response is initiated by three known ER stress transducers: IRE1, PERK and ATF6. These ER-localised transmembrane (TM) proteins posses lumenal stress sensing domains and cytosolic effector domains that collectively activate a gene expression programme regulating the production of proteins involved in the processing and maturation of secreted proteins that enter the ER. However, beyond limiting unfolded protein stress in the ER the UPR has important connections to lipid metabolism that are the subject of this review.